Oxidation‐Resistant and Elastic Mesoporous Carbon with Single‐Layer Graphene Walls. (21st July 2016) - Nishihara, Hirotomo; Simura, Tomoya; Kobayashi, Shunsuke; Nomura, Keita; Berenguer, Raúl; Ito, Masashi; Uchimura, Masanobu; Iden, Hiroshi; Arihara, Kazuki; Ohma, Atsushi; Hayasaka, Yuichiro; Kyotani, Takashi
Abstract : An oxidation‐resistant and elastic mesoporous carbon, graphene mesosponge (GMS), is prepared. GMS has a sponge‐like mesoporous framework (mean pore size is 5.8 nm) consisting mostly of single‐layer graphene walls, which realizes a high electric conductivity and a large surface area (1940 m 2 g −1 ). Moreover, the graphene‐based framework includes only a very small amount of edge sites, thereby achieving much higher stability against oxidation than conventional porous carbons such as carbon blacks and activated carbons. Thus, GMS can simultaneously possess seemingly incompatible properties; the advantages of graphitized carbon materials (high conductivity and high oxidation resistance) and porous carbons (large surface area). These unique features allow GMS to exhibit a sufficient capacitance (125 F g −1 ), wide potential window (4 V), and good rate capability as an electrode material for electric double‐layer capacitors utilizing an organic electrolyte. Hence, GMS achieves a high energy density of 59.3 Wh kg −1 (material mass base), which is more than twice that of commercial materials. Moreover, the continuous graphene framework makes GMS mechanically tough and extremely elastic, and its mean pore size (5.8 nm) can be reversibly compressed down to 0.7 nm by simply applying mechanical force. The sponge‐like elastic property enables an advanced force‐induced adsorption control. Abstract : Oxidation‐resistant and elastic mesoporous carbon consisting of single‐layer graphene walls is prepared. The unique framework realizes a large surface area and minimal number of edge sites, thereby making the material promising for the application in electric double‐layer capacitors. The framework is mechanically tough and greatly elastic, enabling an advanced force‐induced adsorption control.